The Controversies Over Maritain in Chile and Argentina. Precursors of Different Progressive and Conservative Catholicisms (2022)
This work analyzes the controversies over Maritain in Argentina and Chile to read them comparatively, which leads to a medium-term interpretation of these debates as precursors, as trailblazers for different progressive and conservative Catholicisms. These different expressions of Catholicism, forged around the controversies over Maritain, had lasting and profound effects on the historical development of the Catholic Church and its positions on politics in both countries. Thus, our research intends to provide an explanation for both the different expressions of progressive Catholicism, which developed in the two countries in the 1960s and 1970s, as well as the different majority reactions on the part of the Catholic Church during the last military dictatorships in Chile and Argentina. We do not seek to impose a single explanation with this idea, but rather to highlight certain aspects of Catholicism in Argentina and Chile that help to explain the Church's attitude to politics in both countries and which can be seen more clearly in a comparative analysis. In line with Reinhart Koselleck, we argue that the debates on Maritain opened different "expectation horizons" that outlined the possibilities of thinking the political expressions of conservative and progressive Catholicisms in both countries. As medium-term structural factors, these "expectation horizons" help to understand the Catholic Church's reactions to the last military dictatorships in Chile and Argentina.